2022
DOI: 10.3390/ijerph19074166
|View full text |Cite
|
Sign up to set email alerts
|

The New Quadrivalent Adjuvanted Influenza Vaccine for the Italian Elderly: A Health Technology Assessment

Abstract: Background. The elderly, commonly defined as subjects aged ≥65 years, are among the at-risk subjects recommended for annual influenza vaccination in European countries. Currently, two new vaccines are available for this population: the MF59-adjuvanted quadrivalent influenza vaccine (aQIV) and the high-dose quadrivalent influenza vaccine (hdQIV). Their multidimensional assessment might maximize the results in terms of achievable health benefits. Therefore, we carried out a Health Technology Assessment (HTA) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 45 publications
0
39
0
2
Order By: Relevance
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 40 studies included in our systematic review [ 3 , 4 , 5 , 8 , 10 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], seven (17.5%) had a non-European perspective and were conducted in Canada ( n = 1) [ 18 ], the USA ( n = 3) [ 19 , 21 , 42 ], China ( n = 1) [ 36 ], Iran ( n = 1) [ 49 ], and low-income countries (LICs) ( n = 1) [ 32 ]; ten (25%) had a global perspective [ 5 , 10 , 12 , 20 , 22 , 24 …”
Section: Resultsmentioning
confidence: 99%
“…Among the European studies, eight (36.4%) were conducted specifically in Italy [ 3 , 4 , 13 , 31 , 38 , 39 , 43 , 47 ]. In addition, of the 40 articles included in our work, 17 (42.5%) were systematic reviews or literature reviews [ 3 , 5 , 10 , 11 , 12 , 22 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 37 , 41 , 47 , 48 ], ten (25%) were economic evaluations [ 8 , 13 , 19 , 21 , 23 , 26 , 27 , 34 , 44 , 45 ], seven (17.5%) were cross-sectional studies [ 18 , 35 , 36 , 38 , 42 , 43 , 49 ], two studies (5%) were HTA reports [ 4 , 39 ], one study (2.5%) was a nonlinear regression model [ 33 ], and three studies (7.5%) were expert opinions [ 20 , 40 , 46 ]. The main features of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At current, MF59-adjuvanted standard-dose and nonadjuvanted high-dose vaccines appear to have similar effectiveness in preventing seasonal influenza in older adults and therefore no conclusive recommendations on the preference of one vaccine over another could be drawn. Considering both a significant reduction in influenza virus detections observed during the ongoing COVID-19 pandemic (WHO, 2022) and the fact that both aQIV and hdQIV were authorized in 2020 (Calabrò et al, 2022;Cicchetti et al, 2021), it is unlikely that new retrospective (e.g., seasons 2020/21 and 2021/22) rVE studies with more specific endpoints will be available soon. Head-to-head RCTs and large multi-season publicly funded observational studies with more specific outcomes are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although this approach may be justified from the point of view of the vaccine procurement, it may lead to significant between-region differences in vaccination policies 6 (Bonanni et al, 2018;Calabrò et al, 2020). The use of both aQIV (Calabrò et al, 2022) and hdQIV (Cicchetti et al, 2021) in the Italian elderly has recently undergone the process of full health technology assessment (HTA). Both vaccines have been demonstrated effective, safe and of valuefor-money; however, these evaluations were mostly conducted through the prism of comparison with sdSIVs, which were considered as standard-of-care.…”
Section: Introductionmentioning
confidence: 99%